May I Borrow a Stapler? Is This All Students Ask at the Service Desk in a University Library? - Lamøy, Liv Inger; Kilvik, Astrid (Evidence Based Library and Information Practice, 2021)
Objective – The objective of the study is to increase the knowledge about what questions students ask at the library desk and what the purpose is of their use of the desk. Our focus has been on the physical meetings with the students. The aim is to contribute to the discussion on the future development of the library service desk. Methods – We recorded questions asked at the desks to explore how students use the library service desks. The recording, where library staff sorted questions into predefined categories, took place over four weeks between the years 2017–2018. Results – Our recording showed that 63% of the questions asked at the library service desks were about loan services, document delivery, and access to physical and electronic collections. Practical things such as opening hours, lost and found items, and the location of the group study rooms, accounted for 16% of questions. Questions about information technology (IT) made up 8% of questions. Finally, the results showed that 8% of the questions from the four weeks of counting were counselling and guidance questions, and 2% were about literature lists, reference management, and reference management tools. We found more questions about counselling and guidance in the spring weeks and more practical questions in the fall. We did not find any clear connection between the number of questions and the size of the branch libraries. Conclusion – By conducting this study, we have learned more about why students use the library desk. Our study shows that students come to the library desk to ask about a lot more than just borrowing staples. The results from the study will inform the development of the library desk service going forward.